AQ and EQ Related to Lifelong Learning of Undergraduate Students - Sitsira-at, Shuttawwee (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
This research article presents the correlational comparative study aimed at investigating important adversity quotient and emotional quotient related to lifelong learning as well as finding the predictors of lifelong learning of Humanities and Social Sciences undergraduate students. The sample of 1,103 undergraduate students from Humanities and Social Sciences in junior and senior levels was obtained. The sample consisted of 235 male students and 864 female students. The stratified quota random sampling was used. The hypotheses were tested by correlation and multiple regression analysis. Research results show that adversity quotient, emotional quotient and lifelong learning were at rather high level and that positive correlation between students’ adversity quotient, emotional quotient and lifelong learning was statistically significant at .01. Adversity quotient and emotional quotient were the co-variance explanation of the lifelong learning at 43.9%. Results of the total sample from multiple regression analysis indicated that adversity quotient was the first important predictor of lifelong learning, followed by emotional quotient with the accuracy of 40.6% and 35.8%. The highest predictive percentage of 54.1% was found in male students with the same important predictors as the total group.